Sindicalismo, conflictividad y acción directa en las Américas y Europa, de fines del siglo XIX a los años 1980 - Gaudichaud, Franck; Harter, Hélène; Ramos Ramírez, Antonio; Santalena, Elisa (Ariadna Ediciones, 2023)
From the late nineteenth century on, and throughout the twentieth century, more or less sizeable segments of the labour and trade union movement repeatedly engaged in a range of mobilizations that went beyond the legal framework and claimed diverse forms of "radical" and violent direct action, in various political contexts and in the name of different perspectives and ideologies. This multilingual and multidisciplinary collective work addresses several such experiences and several case studies of intense social conflicts that challenged the established order in the Americas as well as in Europe. Our aim is to contribute to a global history of contemporary trade unionism, and particularly to renewing the historiography of direct action on both sides of the Atlantic.